Prospective associations between child screen time and parenting stress and later inattention symptoms in preschoolers during the COVID-19 pandemic - Almeida, Maíra Lopes; Garon-Carrier, Gabrielle; Cinar, Eda; Frizzo, Giana Bitencourt; Fitzpatrick, Caroline (Frontiers in Psychology, 2023)
Introduction Child attention skills are critical for supporting self-regulation abilities, especially during the first years of life. On the other hand, inattention symptoms in preschoolers have been associated with poor school readiness, literacy skills and academic achievement. Previous research has linked excessive screen time with increased inattention symptoms in early childhood. However, most research has only focused on TV exposure and did not investigate this association during the COVID-19 pandemic. This atypical context has increased screen time in children worldwide, including preschoolers. We hypothesize that higher levels of child screen media and parenting stress at age 3.5 will be associated with higher child inattention symptoms at age 4.5. Method This study draws on participants followed longitudinally over the span of 2-years for an investigation of Canadian preschoolers’ screen media use during the pandemic (N = 315, 2020). A follow-up with this sample was completed in 2021 (N = 264). Results Analyses using multiple linear regression, revealed a positive association between child screen time at age 3.5 and inattention symptoms at 4.5 years. Parental stress was also positively associated with child inattention symptoms. Associations were observed above individual (child age, inhibitory control, and sex) and family (parent education and family income) characteristics. Discussion These results confirmed our hypothesis and highlight that preschooler screen use and parenting stress may undermine attentional skills. Since attention is a crucial component for children development, behavior and academic outcomes, our study reinforces the importance for parents of adopting healthy media habits.